Analysis of techniques used by swimmers in the Para-Olympic Games - Persyn, U.; Surmont, E.; Wouters, L.; de Maeyer, J. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
We have not proposed a new system, but we do attempt to show that the present system is unsatisfactory. It can be quite frustrating to the competitors. While it is generally believed that the classification should be made on a functional basis, we propose that it also be made in an aquatic medium. This is necessary in order to compare timed performances in the water. Such a classification might even be specific for each swimming stroke. We consider it of primary importance to identifY some basic general principles rather than be involved in obtaining exact measurements. A videotape recorder has been used to evaluate the hydrodynamic principles applied by paralyzed swimmers. Our study (Surmont, 1974) of able-bodied swimmers on the world class level was the basis for our observational scheme and the grouping of results in this study. All of the swimmers of our test group were participants of the XXI Weltspiele der Geliihmten-Heidelberg, 1972. These Para-Olympic Games took place at the Institut frir Sport und Sportwissenschaft Universitat Heidelberg.